Comprehensive Analysis of Hospitality Service Management in The Digital Era - Komang Indah Cahaya Dewi; Benediktha Aprilliani Midun; Delviola Stefani Paschalia Karnoto; Ketut Dinda Pebriyanti; Ketut Nia Natasha Wira; Kadek Liana Tejawati; Made Kartika Candra Dewi; Ni Kadek Ayu Maharani; Ni Desak Made Santi Diwyarthi (Jurnal Multidisiplin West Science, 2024)
This research aims to study the implementation of service excellence management in the hospitality industry. Using a qualitative approach, data collection methods include in-depth interviews, participant observations, and literature studies. Research bias is minimized through data triangulation techniques. The results of the study found that service excellence management is dynamically evolving in the present era. Hotels are striving to keep up with digital technology developments by engaging in both service implementation and hotel product marketing. Challenges and obstacles lie in human resource skills, technological readiness, and changes in guest preferences.